2020
DOI: 10.1093/pm/pnaa101
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial to Compare Serratus Anterior Plane Block and Erector Spinae Plane Block for Pain Management Following Thoracoscopic Surgery

Abstract: Objective Comparison of ultrasound (US)-guided erector spinae plane block (ESPB) and serratus anterior plane block (SAPB) in video-assisted thoracic surgery (VATS) patients. The primary outcome was to compare perioperative and postoperative (48 hours) opioid consumption. Methods A total of 60 patients were randomized into two groups (N = 30): an ESPB group and an SAPB group. All the patients received intravenous patient-contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 19 publications
0
33
0
Order By: Relevance
“…[ 6 ] Also, other researchers have demonstrated that ESPB had superior analgesia to SAPB after thoracotomy and video-assisted thoracoscopy. [ 7 8 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] Also, other researchers have demonstrated that ESPB had superior analgesia to SAPB after thoracotomy and video-assisted thoracoscopy. [ 7 8 ]…”
Section: Discussionmentioning
confidence: 99%
“…The blockade of the erector spinae plane may have similar analgesic effects to epidural or paravertebral nerve block; however, the potential risk of spinal cord injury is negligible 67–69 . ESPB also has better postoperative analgesic effects compared to other nerve blocks, such as serratus anterior plane block and transversus abdominis plane block 70,71 …”
Section: Discussionmentioning
confidence: 99%
“…73 Randomized studies [74][75][76] and a meta-analysis 77 have demonstrated SAPB improves pain scores, respiratory mechanics, and opioid consumption after VATS but may not be superior to ESPB. [78][79][80] Therefore, SAPB is seen as an alternative to ESPB and PVB until more data are available. 19 In minimally invasive cardiac surgery, SAPB appears to be safe and effective even in the setting of anticoagulation.…”
Section: Peripheral Nerve Blocksmentioning
confidence: 99%